In viaggio con Lauro Messori di Mario Cresci (2017): fotografie d’archivio tra fototesto e libro d’artista - Di Fazio, Angela (Rivista di studi di fotografia. Journal of Studies in Photography, 2019)
The paper investigates the artistic re-use of photographic archival materials and detects the morphological tangency between archive, phototext and artist’s book, highlighting the artist’s ethical responsibility towards History. We will take into consideration Mario Cresci’s photo-book In viaggio con Lauro Messori 1960-2016, in which such a storyboard is constructed on the basis of visual and textual documents produced by geologist Lauro Messori and currently held in the Eni Archive.